Innovative Products and Approaches Used in Nursing Services - Seda Şahan; Ayşegül Yıldız (Association of Nurse Managers, 2020)
The rapid development of technology and information systems today enables innovation to be effective in nursing services. Using innovative products in nursing improves the quality of care, reduces workload, increases evidence-based practices and enables patient procedures to be done in less time. Recently, we encounter different innovative products and approaches in the world and in our country. This review aims to give information about various innovative products applied in the world and in our country.